Islamic economics : basic concepts, new thinking and future directions - Eğri, Taha; Kızılkaya, Necmettin (Cambridge Scholars Publishing, 2015)
Studies conducted in the field of Islamic economics lose their relevance over time. Works examining Islamic economics since the 1970s have been co-opted by the existing economic system and have become limited to a large extent, as they are now only concerned with financial transactions. In fact, ""Islamic economics"" as a concept should actually be conceptualized as an alternative economic system. However, because of the financial and commercial transactions implemented in daily economic life ...